Application of the Ethnoscience-Based Guided Inquiry Learning Model to Improve Science Process Skills in the Material of the Human Excretory System - Hardianti, Astri Nur; Setiawan, Beni (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2023)
This study aims to describe the implementation of learning, students' science process skills, and students' responses after participating in learning with an ethnoscience-based guided inquiry learning model on the material of the human excretory system. This research method uses a Quasi Experimental Design with the design